2023
DOI: 10.1088/1752-7163/acc964
|View full text |Cite
|
Sign up to set email alerts
|

A review on isoprene in human breath

Abstract: We review the literature on isoprene in exhaled breath and discuss the current evidence and models that describe its endogenous origin and consequence for understanding isoprene levels and their variations in exhaled breath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…As presented in Figure b, the isoprene content in exhaled breath is less than 50 ppb in the calm state before exercise. After two minutes of exercise, the content of isoprene rises sharply and then gradually decreases as the exercise time increases, which is related to the metabolic process of isoprene in the human body and that further decreases close to the level before exercise. , These results illustrate that the developed mixed potential sensor holds application prospects in dynamic and real-time monitoring of the physiological metabolic status.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…As presented in Figure b, the isoprene content in exhaled breath is less than 50 ppb in the calm state before exercise. After two minutes of exercise, the content of isoprene rises sharply and then gradually decreases as the exercise time increases, which is related to the metabolic process of isoprene in the human body and that further decreases close to the level before exercise. , These results illustrate that the developed mixed potential sensor holds application prospects in dynamic and real-time monitoring of the physiological metabolic status.…”
Section: Resultsmentioning
confidence: 69%
“…King et al proposed a physiological model of dynamic changes in isoprene concentration and predicted and studied the extrahepatic sources of isoprene. 6,7 Miekisch et al recently revealed that the source of isoprene in humans is attributable to muscle metabolic activity rather than hepatic cholesterol biosynthesis, which laid a theoretical foundation for the application of isoprene in biomarkers. 8−10 Therefore, due to the association of isoprene with muscle metabolism, noninvasive detection of isoprene concentrations in exhaled breath can help to optimize the training of professional athletes as well as guide therapeutic sport interventions for amateur or recreational sports enthusiasts, and is further expected to play a role in unraveling the interactions between exercise, musculoskeletal, and organ metabolism.…”
mentioning
confidence: 99%
“…Isoprene is known as a by-product of cholesterol biosynthesis [13]. It is mainly produced in the muscle tissue [51]. It was speculated that isoprene can be biomarker for diabetes, along with the acetone, but it was not confirmed yet, as isoprene biochemical pathway is not fully clear [51].…”
Section: Analytes Selectionmentioning
confidence: 99%
“…It is mainly produced in the muscle tissue [51]. It was speculated that isoprene can be biomarker for diabetes, along with the acetone, but it was not confirmed yet, as isoprene biochemical pathway is not fully clear [51]. However, there is potential to monitor breath isoprene in some CVD treatments that require lowering the cholesterol level [42].…”
Section: Analytes Selectionmentioning
confidence: 99%
“…The C 5 isoprene unit is the basic building block for terpenoid including steroid hormones biosynthesis that has been biologically essential for ubiquitous terrestrial life forms since billions of years in the course of evolution 9 . It is the second most abundant and endogenous volatile organic compound (VOC) in our exhaled breath 10 . Exhaled concentrations range between 100-300 ppbV in healthy adults.…”
Section: Introductionmentioning
confidence: 99%